In Vitro Study of the Phototherapy Activity of Low-Power Laser AgainstEmbryonic Development and Nit Shell Degradation of Human Head Lice, Pediculus Humanus Capitis - Sallo NajmAl-Marjan, Karwan; Ismael Hassan, Nawroz; Hussein Kamel, Fouad (Al-Nahrain Journal of Science, 2025)
Head lice eggs, called nits, cling to the hair base. Nit removal has become important inhead lice treatment because main insecticides are not 100% nitcidal. The aim of this study is to provide a new method for controlling and treating head lice by inhibiting the development of embryo in their nits (eggs) and nit shell degradation through the use of He-Ne and Nd:YAG laser beams. For this purpose, seventy five nits (ova) of P. humanus capitis were collected from children's hair then all nits were divided on three clean Petri dish, two Petri dish were exposed to He-Ne and Nd:YAG laser then put in incubator at 23±2C° for about a week then followed up the nit hatching rate on daily basis. Results indicate that both types of laser having a powerful role in the inhibition of the head lice nits. The number of hatched nit is equal to 4/25 nits (16%) among Nd-YAG laser exposited nits while the number of hatched nit is equal to 0/25nits (0%) among Gas laser, He-Ne Laser exposited nits in comparing to the control sample, number of hatching egg is equal to 14/25 nits (56%). Chi square association (P. value =0.037) confirmed that the He-Ne laser beam slightly having a stronger effect on the degradation of the head lice nit shell while it is strongly depending on the period of nit exposure.